Special considerations for the management of COVID‐19 pediatric patients in the operating room and pediatric intensive care unit in a tertiary hospital in Singapore. Issue 6 (22nd April 2020) - Thampi, Swapna; Yap, Andrea; Fan, Lijia; Ong, Jacqueline
Abstract: COVID‐19 was first identified in Wuhan, China and is caused by the novel coronavirus SARS‐CoV 2. It has now spread rapidly to over 190 countries and territories around the world and has been declared a global pandemic by the World Health Organization. The virus is spread through droplet transmission and currently has a mortality rate of over 4% globally. The pediatric population has been found to be less susceptible to the disease with the majority of children having milder symptoms and only one pediatric death being reported globally so far. Despite this, strategies need to be put in place to prevent further spread of the virus. We present a summary of the general measures implemented at a large adult and pediatric tertiary hospital in Singapore (National University Hospital) as well as the specific strategies in place for the operating room and pediatric intensive care unit.